Bathymetric Influences on Antarctic Ice‐Shelf Melt Rates. Issue 11 (21st November 2020) - Goldberg, D. N.; Smith, T. A.; Narayanan, S. H. K.; Heimbach, P.; Morlighem, M.
Abstract: Ocean bathymetry exerts a strong control on ice sheet‐ocean interactions within Antarctic ice‐shelf cavities, where it can limit the access of warm, dense water at depth to the underside of floating ice shelves. However, ocean bathymetry is challenging to measure within or close to ice‐shelf cavities. It remains unclear how uncertainty in existing bathymetry datasets affect simulated sub‐ice‐shelf melt rates. Here we infer linear sensitivities of ice‐shelf melt rates to bathymetric shape with grid‐scale detail by means of the adjoint of an ocean general circulation model. Both idealized and realistic‐geometry experiments of sub‐ice‐shelf cavities in West Antarctica reveal that bathymetry has a strong impact on melt in localized regions such as topographic obstacles to flow. Moreover, response of melt to bathymetric perturbation is found to be non‐monotonic, with deepening leading to either increased or decreased melt depending on location. Our computational approach provides a comprehensive way of identifying regions, where refined knowledge of bathymetry is most impactful, and also where bathymetric errors have relatively little effect on modeled ice sheet‐ocean interactions. Plain Language Summary: The bottom of the ocean is not flat, but is a rich, complicated landscape, with vast underwater mountains and valleys. The deep currents which flow over this landscape in the Southern Ocean carry warm waters toward the Antarctic ice sheet, waters capable of driving strong melting under ice shelves – the floating extensions of the ice sheet – which can in turn lead to heightened loss of ice and increased sea levels. However, the way in which this landscape affects melting is not well understood – meaning implications for future ice loss under climate change are difficult to quantify. Using innovative ocean modeling tools, we investigate how patterns of this undersea landscape affect melt rates under Antarctic ice shelves. The results are non‐intuitive: in some locations, a lowered sea bottom would lead to increased melting; while in others, a raised bottom would increase melt. Our model shows that not all landscape features are "equal, " some can play a much larger role in affecting melt rates than others. As the sea bottom is very difficult to measure accurately, we hope that our results will inform future exploration in terms of prioritizing locations to maximize the impact of high‐quality observations. Key Points: Sensitivity of ocean‐driven ice‐shelf melt is investigated using the adjoint of an ocean model Sensitivity of ice‐shelf melt to ocean bathymetry is concentrated on isolated bathymetric features, with wide areas exerting little control Results could be used to prioritize locations of high‐fidelity investigations of sub‐ice‐shelf cavity geometry